LESION STERILISATION AND TISSUE REPAIR OF PRIMARY TEETH - Osadolor, Obehi O; Osadolor, Aisosa J (Nepal Mediciti Medical Journal, 2024)
BACKGROUND Lesion sterilization and tissue repair is also known as non-instrumental endodontic therapy. It involves the use of combination of antibiotics drugs on infected pulp tissue and root canals after getting access to the root canal orifices of the primary teeth. Various combination of antibiotics had been used by some dentists with macrogol , polyethylene glycol, propylene glycol, normal saline or sterile water as the solvent or vehicle used.METHODS An electronic literature search in Science direct and Google was done in December, 2023 using the Population, Concept and Context framework. Search terms and keywords were combined by Boolean operators. Two independent investigators screened titles and abstracts of publications on lesion sterilization and tissue repair of primary teeth. Original research articles, case report, case series with accessible full text were included for review, while review articles, systematic reviews, viewpoints, books, letters, thesis, editorials, book chapters, dissertations and perspectives were among articles excluded during screening. RESULTS One case report was identified from Morocco, a case series from Nigeria and randomized controlled trial from Egypt respectively.CONCLUSIONS Lesion sterilization and tissue repair or non-instrumental endodontic therapy can be a treatment option for primary teeth with infected pulp and root canals .More studies from diverse ethnic population in Africa countries will fill the gaps in knowledge and add to the existing literature.